Mechanisms of protection induced by attenuated simian immunodeficiency virus. II. Lymphocyte depletion does not abrogate protection. - Stebbings, R; Stott, J; Almond, N; Hull, R; Lines, J; Silvera, P; Sangster, R; Corcoran, T; Rose, J; Cobbold, S; Gotch, F; McMichael, A; et al. (1998)
To determine the role that cellular immune responses play in the protection conferred by vaccination with attenuated SIVmac32H (pC8), we have attempted to deplete macaques of their CD8+ cells prior to challenge with wild-type SIVmac32H (pJ5). In two of four pC8-infected macaques, N109 and N112, a transient partial depletion of CD8+ cells by antibody treatment was achieved. On the day of challenge peripheral CD2+CD4-CD8+ cell counts were reduced by 92 and 95%, respectively, in animals N109 and N112 and their lymph nodes revealed a 46 and 58% reduction, respectively, in CD2+CD4-CD8+ cells. Two other pC8-immunized macaques, N110 and N111, treated in the same way, did not show significant depletion of CD8+ cells. None of these four pC8-immunized animals became infected when challenged with 50 MID50 of pJ5. Treatment of a further four pC8-infected and protected macaques and two naive control animals with Campath-1H antibody successfully depleted peripheral CD3+ cell counts by >99% in all treated animals. Campath-1H depletion resulted in enhanced, longer lasting lymphoid depletion. Yet subsequent challenge with 20 MID50 of pJ5 still failed to infect the pC8-immunized animals. All eight of the naive controls, including two Campath-1H-treated animals, became infected following challenge. In summary, partial depletion of circulating CD8+ cells or total lymphocytes prior to challenge failed to abrogate the protection conferred by vaccination with pC8.